Stimulation of NOX2 in isolated hearts reversibly sensitizes RyR2 channels to activation by cytoplasmic calcium - Donoso, Paulin (2014)
The response of ryanodine receptor (RyR) channels to cytoplasmic free calcium concentration ([Ca2 +]) is redox sensitive. Here, we report the effects of a mild oxidative stress on cardiac RyR (RyR2) channels in Langendorff perfused rat hearts. Single RyR2 channels from control ventricles displayed the same three responses to Ca2 + reported in other mammalian tissues, characterized by low, moderate, or high maximal activation. A single episode of 5 min of global ischemia, followed by 1 min of reperfusion, enhanced 2.3-fold the activity of NOX2 compared to controls and changed the frequency distribution of the different responses of RyR2 channels to calcium, favoring the more active ones: high activity response increased and low activity response decreased with respect to controls. This change was fully prevented by perfusion with apocynin or VAS 2870 before ischemia and totally reversed by the extension of the reperfusion period to 15 min. In vitro activation of NOX2 in control SR vesicles mimicked the effect of the ischemia/reperfusion episode on the frequencies of emergence of single RyR2 channel responses to [Ca2 +] and increased 2.2-fold the rate of calcium release in Ca2 +-loaded SR vesicles. In vitro changes were reversed at the single channel level by DTT and in isolated SR vesicles by glutaredoxin. Our results indicate that in whole hearts a mild oxidative stress enhances the response of cardiac RyR2 channels to calcium via NOX2 activation, probably by S-glutathionylation of RyR2 protein. This change is transitory and fully reversible, suggesting a possible role of redox modification in the physiological response of cardiac RyR2 to cellular calcium influx.